(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
There are many engineer, scientist, and ecologist are expressing grave worries about the global climate change. Fossil fuels are used as a source of energy indefinitely. When carbon dioxide, methane, and nitrogen oxides are combusted, they release gases that contribute to the global warming. The warmer the temperature are also a result of deforestation. The danger of global warming has always been the biggest threat to the Earth’s climate. Nonetheless, the majority of people are unaware of climate change and are unaware that it will be a significant issue in the future years. What the majority of people don’t realize is that global warming is happening right now, and we’re already seeing some of its Withering consequences. It has and will continue to have a negative impact on ecosystems and disrupt ecological equilibrium. Because of the perilous consequences of global warming, a few remedies must be developed. The article explains global warming, discusses its origins and risks, and offers a few solutions to this pressing issue. The majority of people are unaware that global warming is occurring right now, yet some of its devastating effects are already being felt. Ecosystems are being affected in a crucial way, and ecological balance may be disturbed as a result. Because of the hazardous consequences of global warming, a few remedies should be developed. The article discusses global warming, its origins and consequences, and offers possible solutions to the pressing problem. Solar, wind, hydro, geothermal, and biomass assets, in particular, would want to be closely monitored. The placement and usage of renewable energy sources is one method for slowing the pace of global warming.